HUBUNGAN DUKUNGAN KELUARGA DENGAN SELF EFICACY PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMDOIALISA DI RSUD KARDINAH - Cuciati, Cuciati; Ulfah, Maria; Ta'adi, Ta'adi (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
Patients with chronic kidney disease (CKD) undergoing hemodialysis experience physical, psychological, and social changes that require strong adaptive capacity toward long-term therapy. Hemodialysis demands a high level of adherence to treatment, fluid restriction, and dietary regulation, which often leads to stress, dependence on others, and a decline in self-efficacy. In this context, family support serves as an external factor that can strengthen patients’ confidence in their ability to manage the treatment process. This study aims to examine the relationship between family support and self-efficacy among CKD patients undergoing hemodialysis at Kardinah General Hospital in Tegal City. The research employed a correlational analytic design with a cross-sectional approach and involved 125 respondents selected through a total sampling technique. Data were collected using validated and reliable questionnaires on family support and self-efficacy. Statistical analysis using the Spearman Rank test revealed that most respondents received good family support and demonstrated moderate to high levels of self-efficacy. A p-value of < 0.05 indicated a statistically significant relationship between family support and self-efficacy. These results highlight the essential role of family involvement in strengthening patients’ self-efficacy to optimize the success of hemodialysis therapy.